Prinsip Keadilan dan Transparansi dalam sistem pembiayaan Bank Syariah untuk Kemaslahatan umat - Khoirotun Nisa Limbong; Muhammad Abdillah Pratama Aminullah; Stefani (SYAHADAT: Journal of Islamic Studies, 2025)
The principles of justice and transparency are the main foundations of Islamic banking operations. These two principles ensure that every financing product and service not only complies with Sharia law but also provides tangible benefits to the wider community. This article comprehensively discusses how the principles of justice and transparency are applied in the Islamic banking financing system, as well as how their implementation contributes to the welfare of the community. This research uses a qualitative approach with a literature analysis of various regulations, journals, and related fatwas. The results of the study indicate that the implementation of these two principles can foster economic stability, increase public trust, and ensure the achievement of the objectives of maqasid al- shariah in the financial sector.